PERAN PENDIDIKAN DALAM MENDORONG GAYA HIDUP SEHAT DAN POLA MAKAN BERGIZI - Riska Banga’ Sulu’; Laurensia Karaseran; Juwinner Dedy Kasingku (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Education about healthy living and nutritious eating is very important, especially for the health and growth of children and teenagers. Not getting enough nutrients can be caused by various factors, including not having enough food, frequent infections, and lack of knowledge about nutrition. This study uses a descriptive-qualitative approach with a literature review method to understand these issues. The results show that education about healthy lifestyles and eating habits needs to be improved at home and school. Increasing awareness and knowledge about nutrition will help ensure that children and teenagers get enough nutrients, which is important for their health and optimal development. Education on healthy living and nutrition is crucial for health and development, especially during the growth stages of children and teenagers. Nutritional deficiencies, influenced by factors like lack of food, repeated infections, and lack of knowledge, can negatively affect physical and mental development. This study aims to explore the importance of health and nutrition education and strategies to increase awareness at home and school. It uses a descriptive-qualitative approach with a literature review method. Data were collected by reviewing literature on health, diet, and nutrition education. The analysis assessed the available information and identified areas needing more attention in health education. The study's results indicate that education on healthy lifestyles and eating habits needs to be improved at home and school. Increasing nutrition knowledge is essential to ensure that children and teenagers receive proper nutrients, supporting their health and optimal development.